Critical crack path assessments in failure investigations - Robert D. Caligiuri (Fracture and Structural Integrity)
This paper presents a case study in which identification of the controlling crack path was critical to identifying the root cause of the failure. The case involves the rupture of a 30-inch (0.76 m) natural gas pipeline in 2010 that tragically led to the destruction of a number of homes and the loss of life. The segment of the pipeline that ruptured was installed in 1956. The longitudinal seam of the segment that ruptured was supposed to have been fabricated by double submerged arc welding. Unfortunately, portions of the segment only received a single submerged arc weld on the outside, leaving unwelded areas on the inside diameter. Post-failure examination of the segment revealed that the rupture originated at one of these unwelded areas. Examination also revealed three additional crack paths or zones emanating from the unwelded area: a zone of ductile tearing, a zone of fatigue, and a zone of cleavage fracture, in that sequence. Initial investigators ignored the ductile tear, assumed the critical crack path was the fatigue component, and (incorrectly) concluded that the root cause of the incident was the failure of the operator to hydrotest the segment after it was installed in 1956. However, as discussed in this paper, the critical path or mechanism was the ductile tear. Furthermore, it was determined that the ductile tear was created during the hydrotest at installation by a mechanism known as pressure reversal. Thus the correct root cause of the rupture was the hydrotest the operator subjected the segment to at installation, helping to increase the awareness of operators and regulators about the potential problems associated with hydrotesting.